Tracing radioactivity from Fukushima in the Northern Pacific Ocean. (March 2016) - Aoyama, M.; Hult, M.; Hamajima, Y.; Lutter, G.; Marissens, G; Stroh, H.; Tzika, F.
Abstract: Following the accident at the Fukushima Daiichi nuclear power plant, a campaign of sampling and measuring anthropogenic radionuclides in North Pacific seawater was set up. The main aim was to study natural processes using these radionuclides as tracers. Because of dilution, the activities of anthropogenic radionuclides at long range were very low and their measurement required advanced pre-concentration techniques and underground gamma-ray spectrometry. Data and metrological aspects of the measurements using HPGe-detectors are presented and discussed. Highlights: The use of anthropogenic radionuclides from Fukushima as tracers is described. Results from plankton and particulate matter are presented. Emergency preparedness for tracer studies is discussed.